(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2009)
The figure of the lay of official response (silencio administrativo) has become the reverse of the legal obligation of the Public Administration in orden to resolve —expressly and in any case— what has been settled in the administrative procedure, and cannot be used as an alibi to make difficult or delay the access of the interested party to the appeals, to the jurisdictional guardianship, until it doesn’t fulfill that legal imperative. Into a State of law cannot be admitted that this transgression can become in the acquisition, by the Administration, of a position of advantage regarding the citizens, to whose service orientates precisely the entire activity of the above mentioned instrumental organization of the executive Power. The institution of the lay of official response is foreseen to offer a solution to the administrative inactivity, but in no case it can appear as a load for the citizen, since this mechanism is conceived from its origin in exclusive benefit of this one.